2012
DOI: 10.1002/joc.3630
|View full text |Cite
|
Sign up to set email alerts
|

Connections of ENSO/IOD and aerosols with Thai rainfall anomalies and associated implications for local rainfall forecasts

Abstract: El Niño/La Niña Southern Oscillation (ENSO), Indian Ocean Dipole (IOD) and aerosols have important roles to play in relation to Southeast Asian rainfall anomalies. This study investigates connections between these factors and local seasonal rainfall anomalies at 17 locations throughout Thailand using ground measurements and satellite observations available from 1980 to October 2011. This research investigates further the usefulness of incorporating these factors into rainfall forecasts. Results from canonical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Map (A) was generated using the generic mapping tools-GMT (http://gmt.soest.hawaii. edu/), and map (B) was redrawn based on aerial photographs before and after 1994 using the data set in Klubseang (2011). 2011, sub-decadal and decadal weakening of the summer monsoon in Thailand has also been associated with ENSO variability, specifically with the increasing number of El Niño events (Bridhikitti, 2013;Hsu et al, 2014;Singhrattna et al, 2005).…”
Section: Regional Settingmentioning
confidence: 99%
“…Map (A) was generated using the generic mapping tools-GMT (http://gmt.soest.hawaii. edu/), and map (B) was redrawn based on aerial photographs before and after 1994 using the data set in Klubseang (2011). 2011, sub-decadal and decadal weakening of the summer monsoon in Thailand has also been associated with ENSO variability, specifically with the increasing number of El Niño events (Bridhikitti, 2013;Hsu et al, 2014;Singhrattna et al, 2005).…”
Section: Regional Settingmentioning
confidence: 99%
“…Several previous studies have indicated that SSTs and ocean indices are associated with the seasonal and interannual climate of Thailand [36][37][38][39], and therefore the variability of rainfall and reservoir inflows may be associated with SST anomalies. Manusthiparom [40] reported that adding SSTs as ANN inputs significantly improved the results of monthly rainfall and runoff forecasting for the Chao Phraya River Basin.…”
Section: Introductionmentioning
confidence: 99%
“…In the VAM, significant SSTs and climatic indices for the inflow each month were plotted and compared to aid in selecting appropriate historical analogues. The idea behind investigating use of SSTs and climatic indices as guidelines for selection of the most suitable historical analogues was derived from the results of several previous studies that indicated that SSTs and climatic indices were associated with the Thai climate and rainfall (e.g., Singharattna et al [36]; Bejranonda and Koch [37]; Chansaengkrachang [38]; Bridhikitti [39]; and Manusthiparom [40]). The improvement in forecasts in this study after incorporation of SSTs and climatic indices supports these previous reports.…”
mentioning
confidence: 99%
“…Other statistical approaches that improve predictability, use only those lagged climate indices that have high correlation with local climate variables. The lag time based climate index approach has been used in regions that have strong tele-connection between global climate indices and local climate variables (Bridhikitti, 2013;Hamlet and Lettenmaier, 1999;Schepen et al, 2012;Räsänen and Kummu, 2013). In Korea, there has been research on seasonal prediction using lagged climate indices, which have high correlation with precipitation and temperature on the Korea peninsula (Kim et al, 2007;Kim and Kim, 2010).…”
Section: Introductionmentioning
confidence: 99%